Depósitos em moeda estrangeira como hedge para investidores brasileiros de longo prazo: Uma aplicaç\~ao da teoria da escolha estratégica de portfólio - Carlos Eduardo Meyer dos Santos; Marcos Antonio C. da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The home bias is observed in the composition of portfolios of different classes of financial assets. The literature offers conflicting arguments about the rationality of this behavior in the case of the portfolios invested in short-term securities, commonly known as currency deposits. In the context of an economy subject to strong volatility, the conventional wisdom suggests that conservative investors should concentrate these deposits on domestic bonds. However, these instruments can be very risky for a long-term investor due to uncertainty about the future short-term interest rate. Not least important, under the assumption of uncovered interest parity, it may be optimal for this investor to maintain foreign currency deposits as a hedge against a deterioration of the domestic investment opportunities. On the root of this argument is the fact that the lower expected return on domestic bonds, as it stimulates the outflow of capital, it is accompanied by real depreciation of the domestic currency. Therefore, the foreign currency deposits reduce the volatility of future wealth as the size of current wealth tends to increase when its expected return decreases. This work evaluates the effectiveness of the foreign currency deposits as an intertemporal hedge for Brazilian long-term investors. The main conclusion is that fairly conservative investors should allocate significant part of these deposits in dollars, pounds and ienes.
Keywords: G11; G15; 330